The research support needs and expectations of emerging researchers employed at the Cape Peninsula University of Technology’s Faculty of Education: a case study - Oosthuizen, Christel (Library and Information Studies Centre (LISC), 2020)
Providing research support services is an important role and function of an academic library. Nationally and internationally, academic institutions are under pressure to improve the quality and quantity of their research outputs. An important aspect in developing a research culture is the provision of effective research support services. As a young research institution, the Cape Peninsula University of Technology (CPUT) invests a lot of time, energy and resources in supporting the development of a research culture. A significant aim of research support services is the progression of emerging researchers to established researchers. CPUT Libraries wishes to play an active role in this regard by providing research support specifically to emerging researchers. The provision of effective research support services however requires services that are aligned with researchers’ unique research support expectations. Without a clear understanding of the unique research support expectations of its researchers, the library will not be able to fulfil an effective research support function. This study obtained a renewed understanding of emerging researchers’ support needs through using a mixed methods approach and a case study research design, focusing on CPUT’s Education Faculty. Emerging researchers’ support needs were determined through a self-administered online questionnaire consisting of open- and close-ended questions. The research life cycle guided the design of the questionnaire. Online questionnaires were sent to all 37 emerging researchers employed in the Education Faculty. A total of 21 responses was received. Data about the perceptions of a group of four librarians and the Education Faculty’s research coordinator about emerging researchers’ most important support expectations were collected through a semi-structured focus group interview and an individual interview respectively. Data collected via the three data collection methods were triangulated to compare the differences and similarities in what was considered emerging researchers’ most important research support expectations. The triangulation of the data led to the creation of a list of the most important research support services that should be provided for emerging researchers at CPUT’s Faculty of Education. The results showed that researchers as well as research support providers regard information provision services as libraries’ most important research support function. Recommendations by the researcher include the active marketing of libraries’ research support services, personalised researcher training, closer cooperation between institutional research support providers and using the research cycle as framework when designing and promoting library research support services. Through the collection of data and the literature reviewed, this study reached an improved understanding of the research support expectations of emerging researchers at CPUT’s Faculty of Education.